2004
DOI: 10.1016/s0012-821x(03)00584-3
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the Antarctic–Phoenix plate system since 15 Ma

Abstract: Joint inversion of magnetic isochron and fracture zone data from the extinct Antarctic^Phoenix spreading system in SW Drake Passage yields seven new finite reconstruction poles. The inversion results are very well constrained for such a short length of plate boundary. Although this is partly because the finite poles are located close to the reconstructed region, the optimum use of fracture zone identifications from satellite-derived free-air gravity data is also important^as the stability of stage poles throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 24 publications
1
80
0
1
Order By: Relevance
“…All this time, and afterwards, accretion continued at the Antarctic-Phoenix Ridge, and the Phoenix plate continued to be subducted beneath the Antarctic Peninsula (Larter and Barker, 1991;Livermore et al, 2000;Eagles, 2003). This situation inevitably led to further ridge crest-trench collisions like those described southwest of the Tula Fracture Zone, but because of the long-offset on the Tula transform fault the first of these later collisions dates from around 20 Ma (Fig.…”
Section: Slab Windows Beneath Cape Horn and North Of The Tula Fracturmentioning
confidence: 94%
“…All this time, and afterwards, accretion continued at the Antarctic-Phoenix Ridge, and the Phoenix plate continued to be subducted beneath the Antarctic Peninsula (Larter and Barker, 1991;Livermore et al, 2000;Eagles, 2003). This situation inevitably led to further ridge crest-trench collisions like those described southwest of the Tula Fracture Zone, but because of the long-offset on the Tula transform fault the first of these later collisions dates from around 20 Ma (Fig.…”
Section: Slab Windows Beneath Cape Horn and North Of The Tula Fracturmentioning
confidence: 94%
“…This system of gravity anomaly lineations is aligned in direct northward prolongation of the eastern West Antarctic Rift System axis through the Bentley Subglacial Trough and the Byrd Subglacial Basin (Figure 2). Geophysical data and detailed plate-kinematic reconstructions have shown that these lineations are primarily associated with the eastern boundary of the former Bellingshausen Plate and tectonic events resulting from a plate reorganisation in the South Pacific around chron C27o (61 Ma) Eagles 2004). The Bellingshausen Plate existed from about 80 to 61 Ma with a strike-slip and transpressional eastern plate boundary at the location of the Bellingshausen Gravity Anomaly (Figures 2, 4).…”
Section: Evidence For Tectonic Activity Across the De Gerlache Gravitmentioning
confidence: 97%
“…15 Ma), which is coeval with Discontinuity M in the Indian Ocean (Niemi et al, 2000), and an unconformity in the South Pacific Ocean (Carter et al, 2004). Several important events occurred in southern South America after 15 Ma, coeval with the re-opening and deepening of the Drake Passage, after 15 Ma (Lagabrielle et al, 2009): first, the margin underwent a massive aggradational phase, which could be associated with major regional subsidence and global third-order highstand intervals in the middle Miocene (Van Andel et al, 1977;Kennett, 1982;Haq et al, 1987;Malumian and Olivero, 2005); second, the end of the compressional tectonics in the Patagonian Cordillera (Barreda and Palamarczuk, 2000); third, a marked rise in sea level over the South American continent (Aceñolaza, 2000); and last, widening of the Drake Passage due to active oceanic spreading along the Phoenix-Antarctic Ridge, from 15 to 8e3 Ma (Livermore et al, 2000;Eagles, 2003), and along the East Scotia Ridge, since 20 Ma (Eagles et al, 2005).…”
Section: Vertical Growth Stage (Iu)mentioning
confidence: 99%